The old and the new formation of euphemisms. Graphical euphemisms formation in electronic discourse - Kudirka, Robertas (Lietuvių kalba, 2012)
Euphemistic substitution occurs due to taboo issues and the most common taboo subjects are physiological actions or their results (motion, sexual intercourse etc) thus the basic function of euphemistic substitution is to soften an offensive, vulgar word. A euphemism is usually defined as a softer, a more neutral substitute for vulgar words, however, such a definition is narrow and not precise as it only indicates one feature of euphemism formation, i.e. correctness, tact. Ascribing euphemisms only to the field of tropes does not reflect their contemporary distribution. Now euphemisms are also used as a linguistic means to conceal facts and manipulate the audience. It is necessary to understand the contemporary usage of euphemisms by two perspectives, i.e. as (1) a neutral word or phrase that is used instead of a synonymous one which is impolite or politically incorrect; and also as (2) individual, occasional contextual substitutions aimed at misrepresenting or concealing facts, real meaffning etc. The new usage of euphemisms is especially relevant to advocate and consolidate new social or political doctrines, "to positively inform" about acts of war carried out by totalitarian regimes, etc. Researchers investigating euphemism usage sometimes do not even mention graphical euphemism formation or do not pay greater attention to it, although in electronic discourse this is a widespread phenomenon. In written language in order to achieve euphemistic effect, a word can be restructured or changed by using non-letter graphical symbols instead of letters, euphemised graphical equivalents can be created. Graphical euphemism formation in manipulative media is not common due to obviousness. Graphical euphemisms as substitutes for obscene vocabulary are most commonly used in internet forums, article comments, interactive chat rooms. When using a graphical euphemism, the automatic check programme does not recognise it as a swearword, a vulgar word and allows inserting such a message. The article distinguishes six types of graphical euphemism formation in electronic discourse: insertion of a letter, insertion of a space, insertion of a non-letter symbol, substitution of a letter with a non-letter symbol, omission of a word part (beginning, middle, ending) and encryption. Together with these types, the cases of occasional and mixed euphemism formation are discussed. The most common type is the omission of a word part (beginning, middle, ending), another common category is that of the substitution of a letter with a non-letter symbol. Less frequent is euphemism formation by inserting a letter, a space or some other non-letter symbol into a word, while the least frequent and unpopular are cases of encrypting a euphemised word.
Keywords: none